A Postmodernist Intertextual Reading of Kalanithi’s When Breath Becomes Air - Ayesha Ashraf (University of Chitral Journal of Linguistics and Literature, 2019)
The present research paper attempts an intertextual reading of When Breath becomes Air by Paul Kalanithi, an Indian-American neurosurgeon and a writer. The term intertextuality was originally coined by Julia Kristeva and it refers to the presence of one or more text/s within a text. It rejects the idea of the closure of meaning and it demonstrates the dialogic state of a text. The current research study is significant as it aims to provide a better understanding of the interdisciplinary connection of fiction with that of any non-fiction text. It further highlights that the use of allusions, reminiscences, aphorisms, and quotations, and aphorisms in the novels that call for many interpretations. The current study has applies the theoretical perspective of postmodern historiographic metafiction proposed by Linda Hutcheon in her book Poetic’s of Postmodernism: History, Theory, Fiction (2003). This research uses intertextuality as a tool to analyze the selected text. Early on, the memoir has been studied with respect to limited perspectives; however, the present study aims to analyze it in the light of postmodernism that refers to a trend of plurality, uncertainty, metafiction, fragmentation, identity crisis, pastiche and intertextuality. The research objective explores the extent to which the writer interweaves fiction into historical texts to generate a postmodern blend in a single narrative. This research is qualitative and descriptive, while textual analysis has been used as a research method. This research ends with the findings and recommendations for the future research.